Cognitive adaptation training for forensic psychiatry inpatients with schizophrenia spectrum diagnoses. Issue 2 (4th March 2022) - Brennan, Courtney; Adams, Kerri; Saikaly, Riley; Lichtenstein, Sidney; Spavor, John; Penney, Stephanie; Simpson, Sandy; Kidd, Sean A.
ABSTRACT: Cognitive deficits affect 70–75% of individuals with schizophrenia and significantly impact functioning. Cognitive Adaptation Training (CAT) is an evidence-based compensatory intervention that improves functioning through personalized environmental supports. Research has explored adaptations to CAT for specific contexts and sub-populations. The present study explored the feasibility and preliminary outcome data for CAT adapted for inpatient forensic psychiatry settings (finCAT). This study employed a single group mixed-method design collecting data at baseline, post-intervention, and 2-months follow-up. Forensic psychiatry inpatients with schizophrenia spectrum diagnoses (N = 18) participated. Outcomes included room organization, self-care, goal attainment, and qualitative interviews with patients (n = 4) and staff (n = 4), as well as secondary measures of unit climate and clinician attitudes. Data analyses with repeated-measures ANOVA revealed a significant effect of time on blind-rated room organization, with significant improvements at post-intervention sustained during follow-up. There were no significant changes to self-care ratings or secondary measures. Qualitative themes identified included (1) improvement in patients' self-care and organization; (2) clinicians' increased awareness of the relationship between cognitive deficits and functional outcomes; (3) improvements beyond self-care and room organization; and (4) increased opportunities for interprofessional collaboration. These results support the feasibility of adapting CAT for inpatient forensic psychiatry settings.